Motivating online language learning: exploring ideal L2 self, grit, and self-efficacy in relation to student satisfaction - Sun, Zhijie; Mu, Bingyu (Frontiers in Psychology, 2023)
This study explores the complex web of motivational factors influencing online learning satisfaction among intermediate-level English as a Foreign Language (EFL) students in mainland China. We examine the roles of ideal L2 self, second language (L2) grit, and online learning selfefficacy in shaping students' satisfaction with their online language learning experience. A diverse sample of 496 EFL students took part in this research, with Structural Equation Modeling employed for data analysis. The results unveil significant and positive relationships between ideal L2 self and L2 grit with online learning satisfaction. Furthermore, online learning self-efficacy emerges as a crucial mediator between ideal L2 self and online learning satisfaction, as well as between L2 grit and online learning satisfaction. These findings enrich our comprehension of the motivational dynamics within online language learning contexts, offering practical insights for educators and instructional designers aiming to enhance students' online learning experiences.